Study on the effects of initial stress and imperfect interface on static and dynamic problems in thermoelastic laminated plates - Yunying Zhou; Jiahuan Liu; Hong Mei; Dinggui Hou; Zhijie Yue; Yunxia Zhang (Science and Engineering of Composite Materials)
Based on the generalized thermoelasticity theory, the influence of initial stress and imperfect thermal interfaces on the static and dynamic problems of the simply supported thermoelastic laminated plate is investigated. Besides adopting the spring-layer model for the elastic field, the thermal conditions at the interfaces are also described as weak or high thermal conducting conditions. By employing the state-space method and introducing the interface transfer matrices for both elastic and thermal fields, this approach is convenient and efficient for multi-layer or thermoelastic coupled structures. Numerical results are presented to verify the correctness of the formulations, and the effects of initial stress and imperfect interfaces on various field variables in the structure under free vibration and static bending are illustrated.